2018
DOI: 10.1080/16506073.2018.1476908
|View full text |Cite
|
Sign up to set email alerts
|

A placebo-controlled randomized trial of D-cycloserine augmentation of cue exposure therapy for smoking cessation

Abstract: Recent studies underscore the importance of studying d-cycloserine (DCS) augmentation under conditions of adequate cue exposure treatment (CET) and protection from reconditioning experiences. In this randomized trial, we evaluated the efficacy of DCS for augmenting CET for smoking cessation under these conditions. Sixty-two smokers attained at least 18 hours abstinence following 4 weeks of smoking cessation treatment and were randomly assigned to receive a single dose of DCS (n=30) or placebo (n=32) prior to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Indeed, studies controlling for between-session sensitization experiences reported positive effects for DCS-augmented CET in patients with AUD [110] and TUD [122]. Moreover, all reported studies suffer from small sample sizes, making it difficult to detect the presumably small effect suggested from clinical trials in anxiety disorders [102].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, studies controlling for between-session sensitization experiences reported positive effects for DCS-augmented CET in patients with AUD [110] and TUD [122]. Moreover, all reported studies suffer from small sample sizes, making it difficult to detect the presumably small effect suggested from clinical trials in anxiety disorders [102].…”
Section: Discussionmentioning
confidence: 99%
“…Although groups did not differ in reported smoking behavior, expired carbon monoxide in the DCS group was significantly lower at the first of two follow-up sessions (d = 1.1). In line with this, Otto et al [106] investigated DCSaugmented CET after treatment-seeking TUD patients completed a smoking cessation treatment, showing reduced subjective craving and physiological reactivity to smoking cues (d = 0.8-1.21), but only a tendency of high-er abstinence rates at 6-week follow-up in DCS-treated participants relative to placebo. However, a third study found no effect of DCS + CET on cue-induced craving or attentional bias, but a statistical trend indicating DCS might have reduced tonic craving at 2-week follow-up, as assessed in the emotional subscale of the Tobacco Craving Questionnaire [107].…”
Section: D-cycloserine-augmented Cue Exposure Therapymentioning
confidence: 94%
“…NMDA receptor agonists (D-serine and D-cycloserine) facilitate the extinction of drug-induced conditioned place preference and reduce reinstatement ( Botreau et al, 2006 ; Myers and Carlezon, 2012 ; Hammond et al, 2013 ). In humans, D-cycloserine has been assessed prior to extinction sessions, with poor results in alcohol-dependent subjects and cocaine addicts ( Hofmann et al, 2012 ; Price et al, 2013 ; Santa Ana et al, 2015 ) and promising results in smokers ( Santa Ana et al, 2009 ; Kamboj et al, 2012 ; Otto et al, 2019 ). Clinical studies have used cue exposure therapy based on the extinction of the conditioned responses elicited by environmental stimuli.…”
Section: Clinical Implications Of Memory Updatingmentioning
confidence: 99%
“…The optimized cue exposure therapy procedure includes pre-exposing subjects to cues before extinction training begins (i.e., a memory retrieval period) and administering an appropriate dose of D-cycloserine prior to sufficiently long extinction sessions that are typically spaced at weekly intervals [10,17]. With an optimized procedure, D-cycloserine improved cueexposure therapy for alcohol [18] and nicotine [19] to reduce craving and forestall relapse in alcohol-abusing individuals and smokers, respectively. Use of drug memory retrieval methods prior to extinction training also was shown to reduce cue-induced heroin craving in people and reinstatement of cocaine seeking in rats [20][21][22].…”
Section: Introductionmentioning
confidence: 99%